(untitled) (ALUSTATH JOURNAL FOR HUMAN AND SOCIAL SCIENCES, 2020)
Reduplication can be defined as a morphological process where the root or stem of a word (or part of it) is repeated exactly or with a slight change. It can be found in many world languages with various types and uses. This paper investigates reduplication in terms of phonology, morphology, and semantics in some selected verses of the Glorious Qur’an concerning its kinds and its translation into English. The main problem of the present research is concerned with the way of translating reduplication concerning the Glorious Quran. Different interpretations of reduplication are adopted to show the efficiency and the rhetorical functions of these forms. More specifically, four translations of Pickthall, Yusuf Ali, Shakir, and Arberry are examined to find the strategies and methods used to translate reduplication accurately and appropriately. It is concluded that some translators succeeded in translating reduplication, whereas others could maintain neither the functions nor the impacts of such forms in English. However, it is challenging to render reduplication phonologically and morphologically into English due to the eloquence and inimitability of the Glorious Qur’an.